Skin anisotropy: Finding the optimal incision line for volar forearm in males and females. (December 2021) - Rosicka, K.; Hill, M.; Wdowski, M.M.
Abstract: Purpose: Proper understanding of skin biomechanics, viscoelasticity and investigation of skin tension vectors is necessary to find optimal incision lines. Great tension across a healing wound after any surgical procedure might lead to forming hypertrophic scars. The aim of the study was to investigate tension lines in volar forearm skin in young males and females, in order to ensure best incision line. Methods: Five biomechanical and viscoelastic parameters were measured using a hand-held myotonometer: Oscillation Frequency [Hz], Dynamic Stiffness [N/m], Logarithmic Decrement of tissue's natural oscillation, Mechanical Stress Relaxation Time [ms], and Creep. Measurements were taken in four different directions; Along Forearm, Across Forearm, Along Langer's Line and Across Langer's Line. Results: Significant main effects for direction were found for Oscillation Frequency (p < 0.001, η 2 = 0.371) [Hz], Dynamic Stiffness (p < 0.001, η 2 = 0.522) [N/m], Logarithmic Decrement (p < 0.001, η 2 = 0.083), Mechanical Stress Relaxation Time (p < 0.001, η 2 = 0.494) [ms] and Creep (p < 0.001, η 2 = 0.480). For each parameter except for logarithmic decrement results obtained Along Langers Line and Across Forearm were significantly different to Across Langers Line and Along Forearm (p < 0.001, d = −2.76 – 2.66). Significant main effects for sex were found for logarithmic decrement Along Forearm (p < 0.001, d = 1.698) and Across Langer's Line (p = 0.021, d = 1.697). Conclusions: Our results suggested that optimal incision line for this age group in males and females could potentially be performed diagonally i.e. Across Langer's Line or parallel i.e. Along Forearm to forearm axis. These directions would provide the lowest tension across a healing wound and possibly minimalize the risk of hypertrophic scarring post incision.